PELUANG DAN TANTANGAN MENINGKATKAN KETERLIBATAN WARGA NEGARA MUDA DALAM MEMPROMOSIKAN PERDAMAIAN DI MASYARAKAT - Rista Ayu Mawarti (Universitas Negeri Malang, 2023)
OPPORTUNITIES AND CHALLENGES OF INCREASING THE INVOLVEMENT OF YOUNG CITIZENS IN PROMOTING PEACE IN COMMUNITIESIn the current era where everyone has the convenience of interacting and communicating with each other across regional boundaries, student interest in gaining learning experiences not only in the